2020
DOI: 10.1002/smll.202003834
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Cell Membrane Camouflaged Semi‐Yolk@Spiky‐Shell Nanomotor for Enhanced Cell Adhesion and Synergistic Therapy

Abstract: Cell adhesion of nanosystems is significant for efficient cellular uptake and drug delivery in cancer therapy. Herein, a near‐infrared (NIR) light‐driven biomimetic nanomotor is reported to achieve the improved cell adhesion and cellular uptake for synergistic photothermal and chemotherapy of breast cancer. The nanomotor is composed of carbon@silica (C@SiO2) with semi‐yolk@spiky‐shell structure, loaded with the anticancer drug doxorubicin (DOX) and camouflaged with MCF‐7 breast cancer cell membrane (i.e., mC@S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 56 publications
0
49
0
Order By: Relevance
“…Zhou et al demonstrated how cell membrane coating, sourced from MCF-7 cancer cells, promoted the selfthermophoretic motion of NIR light-driven semi-yolk@spiky shell carbon@silica nanomotors loaded with DOX to treat cancers (Figure 10A). [98] Such MC@SiO2@DOX motors were assessed in their photothermal and chemotherapeutic therapy of breast cancer (Figure 10B). The cell membrane camouflaged the motors, reduced bio-adhesion, and thus lowered their resistance to propel in the viscous cell culture media.…”
Section: Photothermal Therapymentioning
confidence: 99%
“…Zhou et al demonstrated how cell membrane coating, sourced from MCF-7 cancer cells, promoted the selfthermophoretic motion of NIR light-driven semi-yolk@spiky shell carbon@silica nanomotors loaded with DOX to treat cancers (Figure 10A). [98] Such MC@SiO2@DOX motors were assessed in their photothermal and chemotherapeutic therapy of breast cancer (Figure 10B). The cell membrane camouflaged the motors, reduced bio-adhesion, and thus lowered their resistance to propel in the viscous cell culture media.…”
Section: Photothermal Therapymentioning
confidence: 99%
“…Upon exposure to a NIR light, a thermal gradient across the NPs is generated due to asymmetric carbon core, which propels their motion by self-thermophoretic mechanism (Figure 10B). [77] Recently, our group has also fabricated an asymmetric multilayer-sandwich mesoporous nanobottle-shaped Figure 10. Construction of core-shell structured mesoporous MNMs.…”
Section: Functional Mesoporous Materials As Shellsmentioning
confidence: 99%
“…In a unique study, Zhau et al showed, for the first time, the use of core-shell NIR light-driven nanocarrier to enhance the thermophoretic movement of the particle inside the cell. [63] The Spiky-shell silica nanocarrier with carbon core is used, which has NIR light-driven thermo-phoretic properties. Dox is loaded as a drug, and the MCF-7 cell membrane was used to coat the nanocarrier.…”
Section: Homotypic Targeting Based Chemotherapymentioning
confidence: 99%